Effects of Different Plyometric Training Frequencies on Components of Physical Fitness in Amateur Female Soccer Players - Ramirez-Campillo, Rodrigo; García-Pinillos, Felipe; García-Ramos, Amador; Yanci, Javier; Gentil, Paulo; Chaabene, Helmi; Granacher, Urs (Frontiers in Physiology, 2018)
Plyometric jump training (PJT) is a frequently used and effective means to improve amateur and elite soccer players' physical fitness. However, it is unresolved how different PJT frequencies per week with equal overall training volume may affect training-induced adaptations. Therefore, the aim of this study was to compare the effects of an in-season 8 week PJT with one session versus two sessions per week and equal training volume on components of physical fitness in amateur female soccer players. A single-blind randomized controlled trial was conducted. Participants (N=23; age, 21.4±3.2 years) were randomly assigned to a one session PJT per-week (PJT-1, n=8), two sessions PJT per-week (PJT-2, n=8) or an active control group (CON, n=7). Before and after training, participants performed countermovement jumps (CMJ), drop-jumps from a 20-cm drop-height (DJ20), a maximal kicking velocity test (MKV), the 15-m linear sprint-time test, the Meylan test for the assessment of change of direction ability (CoDA), and the Yo-Yo intermittent recovery endurance test (Yo-YoIR1). Results revealed significant main effects of time for the CMJ, DJ20, MKV, 15-m sprint, CoDA, and the Yo-YoIR1 (all p<0.001; d=0.57-0.83). Significant group×time interactions were observed for the CMJ, DJ20, MKV, 15-m sprint, CoDA, and the Yo-YoIR1 (all p<0.05; d=0.36-0.51). Post-hoc analyses showed similar improvements for PJT-1 and PJT-2 groups in CMJ (∆10.6%, d=0.37; and ∆10.1%, d=0.51, respectively), DJ20 (∆12.9%, d=0.47; and ∆13.1%, d=0.54, respectively), MKV (∆8.6%, d=0.52; and ∆9.1%, d=0.47, respectively), 15-m sprint (∆8.3%, d=2.25; and ∆9.5%, d=2.67, respectively), CoDA (∆7.5%, d=1.68; and ∆7.4%, d=1.16, respectively), and YoYoIR1 (∆10.3%, d=0.22; and ∆9.9%, d=0.26, respectively). No significant pre-post changes were found for CON (all p>0.05; ∆0.5-4.2%, d=0.03-0.2). In conclusion, higher PJT exposure in terms of session frequency has no extra effects on female soccer players’ physical fitness development when jump volume is equated during a short-term (i.e., 8 weeks) training program. From this, it follows that one PJT session per week combined with regular soccer-specific training appears to be sufficient to induce physical fitness improvements in amateur female soccer players.